Miniature Circuit Breaker Trip Detector - Mokhzani Aris, Dameer Aris; Zinal, Nabiah (Multidisciplinary Applied Research and Innovation, 2025)
This project presents a Miniature Circuit Breaker (MCB) Trip Detector system designed to monitor electrical circuits using a relay AC coil 240V integrated with an ESP32 microcontroller. The system aims to detect anomalies such as overloads and short circuits, providing real-time notifications via Telegram upon detecting an MCB trip. Performance evaluation revealed the system's high reliability in accurately identifying faults and its effectiveness in minimizing downtime through swift fault notification and detailed diagnostic information. Challenges included microcontroller processing capabilities for complex tasks, suggesting areas for future improvement. Research opportunities include enhancing alert technology, upgrading microcontroller capabilities, exploring IoT integration, and developing predictive maintenance algorithms for broader applications in residential and industrial settings.